From Understanding Cellular Function to Novel Drug Discovery: The Role of Planar Patch-Clamp Array Chip Technology - Py, Christophe; Martina, Marzia; Diaz-Quijada, Gerardo A.; Luk, Collin C.; Martinez, Dolores; Denhoff, Mike W.; Charrier, Anne; Comas, Tanya; Monette, Robert; Krantis, Anthony; Syed, Naweed I.; Mealing, Geoffrey A. (Frontiers in Pharmacology, 2011)
All excitable cell functions rely upon ion channels that are embedded in their plasma membrane. Perturbations of ion channel structure or function result in pathologies ranging from cardiac dysfunction to neurodegenerative disorders. Consequently, to understand the functions of excitable cells and to remedy their pathophysiology, it is important to understand the ion channel functions under various experimental conditions – including exposure to novel drug targets. Glass pipette patch-clamp is the state of the art technique to monitor the intrinsic and synaptic properties of neurons. However, this technique is labor-intensive and has low data throughput. Planar patch-clamp chips, integrated into automated systems, offer high throughputs but are limited to isolated cells from suspensions, resulting in questionable models of true physiological function, and are unsuitable for studies involving neuronal communication. Multi-electrode arrays (MEA), in contrast, have the ability to monitor network activity by measuring local field potentials from multiple extracellular sites, but specific ion channel activity is challenging to extract from these multiplexed signals. Here we describe a novel planar patch-clamp chip technology that enables the simultaneous high resolution electrophysiological interrogation of individual neurons at multiple sites in synaptically connected neuronal networks, thereby combining the advantages of MEA and patch-clamp techniques. Each neuron can be probed through an aperture that connects to a dedicated subterranean microfluidic channel. Neurons growing in networks are aligned to the apertures by physisorbed or chemisorbed chemical cues. In this review, we describe the design and fabrication process of these chips, the approach to the chemical patterning for cell placement, and present physiological data from cultured neuronal cells.